Empati Perawat Pasien Gangguan Jiwa - Djati, Imansyah (2016)
This research purpose to identify how the empathy contribution at soul interfere nursing duty and how empathy forms done by nurse to soul interfere patient. To reach the purpose it, researcher was using qualitative approach. Their approach was used at 3 nurses of soul interfere patient. Pursuant to research result found that empathy have contribution to soul interfere nursing among others: watering down nurse relate to the patient, finding address of patient family, obtaining aid from surounding citizen, adapting to patient, becoming more patient, improving nurse selfregard at patient, x'self.improving understanding. As for forms of nurse empathy to soul interfere patient by afective, cognate, and afactive and realized in the form of emphatic concern or attention through attitude (non verbal) and also communication (verbal). As for forms of nurse empathy cognately covering: - assuming workplace in the place of house, kept quiet and bear, considering duty and responsibility as nurse, considering darling others existence and nurse supporting. While empathy forms done a nurse through the communications covering: - Communications construct each other trust relation (BHSP), communications as effort persuade to take medicine, communications as attention form (emphatic concern), communications comprehend the patient character, communications as motivation to patient, communications persuade the patient meritoriously and reward, communications as therapy converse the patient, communications as effort viewpoint comprehend (Perspective Taking) mind and patient feeling. In its duty was nurse sometimes require to x'self conceive (Fantacy) become like patient, feeling natural disability and accident patient to be continued for impelled an intention to help and give the best service. Key word: empathy, empathy contribution, empathy forms, nurse of interfere soul patient.